Analisis Risk Profile dan Pengaruhnya Terhadap Tingkat Pengembalian Aset pada Perusahaan Perbankan BUMN yang Terdaftar Di Bursa Efek Indonesia Periode 2015 – 2019 - Muhammad Ridho Almuhdhor (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to analyze how the risk profile level of state-owned banking companies in the period 2015-2019 and test how it affects the rate of return of assets simultaneously and partially. This study uses census techniques that make all state-owned banking companies in the period 2015-2019 as a sample of research. By using multiple linear regression analysis tools and overall statistical testing (F test) and partial (t test), it can be concluded that based on the risk profile level of state-owned banking companies in the period 2015-2019, where Credit Risk shows state-owned banks on healthy criteria, Market Risk and Operational Risk shows state-owned banks on very healthy criteria while Liquidity Risk shows state-owned banks on fairly healthy criteria. Then based on simultaneous research Credit Risk, Market Risk, Liquidity Risk and Operational Risk have a significant positive effect on the return of assets, while partially Credit Risk has a negative effect insignificant, Market Risk and Liquidity Risk have a significant positive effect while Operational Risk has a significant negative effect on the return rate of assets.